Institutional reflexivity - Manfred Moldaschl (Technische Universität Chemnitz, Lehrstuhl für Innovationsforschung und nachhaltiges Ressourcenmanagement, 2007)
How can we understand the innovativeness of firms or organizations in general, and how should we assess it in terms of nontechnological innovation? My paper deals with these two questions. The ability of companies to adapt to new circumstances, to create new products, processes and new knowledge, has been conceptualized in many approaches. Some of them simply define a list of (critical) success factors or (key) performance indicators as tools for ranking and evaluation, without any theoretical reference. Others, like the resource-based or capability-based approach(es), work with theoretical references, but are still very weak in operationalizing of what they call capability. My paper gives a critical description of this situation and offers a new proposal to classify and to measure the inclination of organizations to innovate in all dimensions. This proposal roots in pragmatistic thinking as represented in the theory of reflexive modernization and in the pragmatist version of organizational learning theory. Empirically, it has been applied merely in case studies yet. A survey project is in preparation.
urn:nbn:de:bsz:ch1-200701809
Keywords: 330; Absorptive Capacity; Competence-Based View; Dynamic Capabilities